Nilai Moderasi Beragama dalam Buku Ajar SKI pada Peserta Didik Madrasah Aliyah : Penelitian - Arafat, Imam Agus; Khuriyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The research aimed to analyze the values of religious moderation contained in the SKI student textbook for tenth-grade students of Madrasah Aliyah for the odd semester published by the Ministry of Religious Affairs in 2020, focusing on three main topics: the Development of Islam during the Prophet Muhammad’s period in Makkah, the Development of Islam during the Prophet Muhammad’s period in Madinah, and the Conquest of Makkah (Fathul Makkah). The study employed a qualitative approach with a library research design, using the SKI textbook as the primary source of data. The data were examined through content analysis and discourse analysis, following several stages, including data collection, data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the religious moderation values presented in the learning material. The results of the research indicated that the textbook substantially incorporated religious moderation values in a structured manner, consisting of eight values in the Makkah period topic—Tawasuth, I’tidal, Syuro, Islah, Muwathanah, Qudwah, La’Unf, and ‘Urf; six values in the Madinah period topic—Tawasuth, I’tidal, Tasamuh, Syuro, Islah, and Qudwah; and four values in the topic of the Conquest of Makkah—Tawasuth, I’tidal, Tasamuh, and Islah, all of which demonstrated efforts to strengthen religious moderation through SKI learning at the Madrasah Aliyah level.